Optimal resonant asymptotics of wakefield excitation in plasma by non-resonant sequence of electron bunches - Maslov, V.I.; Bilokon, E.O.; Bilokon, V.O.; Levchuk, I.P.; Onishchenko, I.N. (Вопросы атомной науки и техники, 2019)
Resonant asymptotics of wakefield excitation in plasma by non-resonant sequence of relativistic electron bunch-es has been numerically simulated. It has been shown that in resonant asymptotics at optimal parameters the wake-field is excited with the maximum growth rate and the amplitude of the excited wakefield is the largest. Чисельно промодельована резонансна асимптотика збудження в плазмі кільватерного поля нерезонансною послідовністю релятивістських електронних згустків. Показано, що в резонансній асимптотиці при оптимальних параметрах кільватерне поле збуджується з максимальним інкрементом, а амплітуда збуджуваного кільватерного поля найбільша. Численно промоделирована резонансная асимптотика возбуждения в плазме кильватерного поля нерезонансной последовательностью релятивистских электронных сгустков. Показано, что в резонансной асимптотике при оптимальных параметрах кильватерное поле возбуждается с максимальным инкрементом, а амплитуда возбуждаемого кильватерного поля наибольшая.